2014
DOI: 10.1210/jc.2013-3919
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Trial of Intravenous Glucocorticoids Therapy With Different Protocols for Patients With Graves' Ophthalmopathy

Abstract: The weekly protocol of iv methylprednisolone therapy is more efficient and safer than the daily protocol for patients with active moderate-to-severe GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
4
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 28 publications
4
86
4
10
Order By: Relevance
“…To the best of our knowledge, there were 2 randomized clinical trials investigating the optimal dose and schedule of iv GC therapy [16,17]. When Bartalena et al compared the safety and efficacy of 3 low-dose iv GC regimens (cumulative doses of 2.25 g, 4.98 g, and 7.47 g), they concluded that the higher-dose regimen provided a short-term advantage in efficacy, but had slightly greater toxicity [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there were 2 randomized clinical trials investigating the optimal dose and schedule of iv GC therapy [16,17]. When Bartalena et al compared the safety and efficacy of 3 low-dose iv GC regimens (cumulative doses of 2.25 g, 4.98 g, and 7.47 g), they concluded that the higher-dose regimen provided a short-term advantage in efficacy, but had slightly greater toxicity [16].…”
Section: Discussionmentioning
confidence: 99%
“…Since this is not a standard method for comparing SIRs from different MRI scanners, this approach requires further verification. We did not define the outcome of GO by evaluating a combination of changes in ophthalmic parameters because we were not able to collect complete information about ophthalmic parameters that were evaluated in prior large prospective studies [16,17]. For example, we were not able to obtain grades in each class of the NOSPECS classification from the patients' medical records.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of different IV glucocorticosteroid therapy protocols are still under debate. Presently, there are no generally accepted recommendations or guidelines for treatment of GO [20,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized study, this schedule was compared with a shorter regimen of the same cumulative dose (daily infusion of 0.5 g for 3 days over 2 weeks, followed by a daily infusion of 0.25 g for 3 days over 2 weeks) [69]. The latter protocol was, however, associated with lower efficacy compared to the standard protocol (response rate of 41 vs. 77%; p = 0.0025) and toxicity was higher [69].…”
Section: Recommendationsmentioning
confidence: 99%